Assemble: The Artifact as a Collaborative Tool in Knit Design Research. (1st September 2020) - Scott, Jane; Gaston, Elizabeth
Abstract: This paper presents a new perspective on the role of the artifact in knit design research. The artifact is presented as a stimulus for interdisciplinary research where practice based enquiry provides only part of the required methodological approach. Reporting on a major collaboration between the curator of the Oriental Collection at The Royal Armories, Leeds, and researchers from the School of Design at The University of Leeds, this paper pursues two key trajectories. Firstly, the paper outlines how the artifact can be used as a design stimulus for interdisciplinary collaboration. This is assessed across multiple stages of design and through the production of several perspectives on key thematic ideas. Secondly, the paper reports on how collaboration, specifically in the development of these alternative perspectives, can lead to materials innovation. These two points of discussion are contextualized with reference to interior architectural installation, Inflection, and supported by analysis of The Knitting Machine, Cocoon and knitted exterior installation Configure . Findings highlight how the use of artifacts enables practitioners to adapt thinking using material practice in order to generate new knowledge.